Predicting vitamin E and C consumption intentions and behaviors among factory workers based on protection motivation theory - Sahar Mohammad Nabizadeh; Parvaneh Taymoori; Mohammad Saleh Hazhir; Mehra Shirazi; Daem Roshani; Behzad Shahmoradi (Komiyama Printing Co. Ltd, 2018)
Abstract Background Study of antioxidant vitamin consumption behavior, especially in high-risk groups with high exposure to toxic metals to reduce metal toxicity, is emphasized. This study aims to examine the structural relationships between knowledge, protection motivation theory constructs, and vitamin E and C consumption behavior among cement factory workers. Methods Protection motivation theory and food frequency questionnaires were completed by 420 factory workers. Data were subjected to structural equation modeling to examine associations between knowledge, protection motivation theory constructs, and vitamin E and C consumption behavior. Efficacy of current recommended models was also explored. Results Structural equation modeling showed high explained variance within the constructs of protection motivation theory for vitamin E and C consumption behavior and intention (56-76%). The overall fit of the structural models was acceptable for both vitamin E and C behavior. Knowledge, self-efficacy, response efficacy, and perceived vulnerability predicted intention, which in turn predicted vitamin consumption behavior. Significant relationships between knowledge and self-efficacy, response efficacy, perceived vulnerability, and perceived severity were also found, while self-efficacy and response efficacy showed significant relationships with vitamin E and C consumption behavior. Conclusions Considering that response efficacy, self-efficacy, and intention showed as strong predictors of vitamin E and C consumption behavior, specific attention should be paid to coping appraisals and intention when designing intervention plans. Additionally, establishing the predicting role of knowledge for protection motivation theory constructs and protective behaviors should be integrated into intervention programs.